Absolute illiteracy in European Union policies: Exploring the intersections of gender, migration and education - Barroso, M. M. (Géneros: Multidisciplinary Journal of Gender Studies, 2024)
In the context of a study focused on the absolute illiteracy of migrant women in Europe, this article assesses the extent to which European Union policy instruments on gender, migration and education incorporate an intersectional perspective. The analysis was based in the content analysis of a selected group of EU policy documents and included i) the close and iterative reading and thematic codification of the texts; ii) the word frequency counting of relevant terms; and iii) the assessment of intersectionality through a set of quality criteria. Apart from revealing the invisibility of absolute illiteracy as a policy problem, results confirm previous evidence showing that the presence of intersectional approaches in EU public policy is still marginal. Some attempts to address the intersectionality of gender, migration or education inequalities have been identified in the selected documents, but a comprehensive policy framework to understand and address those inequalities is still lacking. The article adds up to the existing scholarship claiming for more inclusive policies in contemporary European societies.